Pituitary Adenoma Presenting as Anorexia Nervosa: A Case Report (Journal of Psychiatrists' Association of Nepal, 2017)
Anorexia nervosa is a syndrome characterized by severe weight loss and preoccupation of distorted body image with resulting complications due to starvation. In most of the typical cases of anorexia nervosa, neuroimaging is not done. However, with increasing evidence of intracranial lesions associated with eating disorders including anorexia nervosa, neuroimaging is indicated in almost all cases. We present a case of a 17-year-old female who was admitted initially with the diagnosis of anorexia nervosa (restricting type) and later found to have pituitary adenoma.